Tests of a reinforced concrete frame beam subjected to seismic-type loading = Badania rygli ram żelbetowych poddanych obciążeniom typu sejsmicznego - Korentz, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The experimental results from reversed cyclic loading tests on twelve exterior reinforced concrete beam-column joints are presented. The primary variables were the ratio of positive to negative reinforcement and the stirrup spacing of beams. The specimens were subjected to cyclic load reversal at deflection levels intended to represent the levels that could be obtained during a moderate or severe earthquake. The results are compared with the existing design recommendations and investigating the behavior of reinforced concrete beam. A reduced stirrup spacing and an increased ratio of positive to negative steel at the face of the support improves cyclic performance of beams.
Keywords: ramy żelbetowe; węzły zewnętrzne; obciążenia sejsmiczne; reinforced concrete; beams; cyclic loads; earthquake-resistant structure; ductility